2012
DOI: 10.2174/138955712802761988
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis as a therapeutic target in breast cancer

Abstract: Current evidence indicates that angiogenesis plays an important role in the pathogenesis of several malignancies, including breast cancer. Bevacizumab is a monoclonal antibody that targets the vascular endothelial growth factor (VEGF). Recent clinical data have demonstrated that the addition of bevacizumab to first-line chemotherapy improves the progression-free survival of patients with advanced breast cancer. This review presents an update on the role of bevacizumab, as well as other anti-angiogenic agents i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Angiogenesis, a requisite for tumor growth, is the net result of a balance of angiogenic and antiangiogenic factors ( 1 3 ). Neoangiogenesis has remained a promising cancer therapeutic target for decades ( 4 6 ). However, the efficacy of anti-angiogenic therapies, mainly based on blocking VEGF function, has been limited in the clinical setting ( 7 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis, a requisite for tumor growth, is the net result of a balance of angiogenic and antiangiogenic factors ( 1 3 ). Neoangiogenesis has remained a promising cancer therapeutic target for decades ( 4 6 ). However, the efficacy of anti-angiogenic therapies, mainly based on blocking VEGF function, has been limited in the clinical setting ( 7 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that tumours induce sprouting angiogenesis from surrounding vasculature, which is essential for tumour growth [2,28,29]. Our previous data have shown potential roles of YB1 CTD in proliferation and differentiation VSMCs, which are major components of vessel walls and play vital roles in vascular formation, remodelling and angiogenesis [20,30,31].…”
Section: Discussionmentioning
confidence: 94%